Pengaruh Rasio Keuangan terhadap Return Saham dengan Kebijakan Dividen Sebagai Variabel Moderasi pada Perusahaan yang Terdaftar di BEI - Rosalina, Sella; Adnan Pratama, Ifanny (LPPM STIE PPI, 2024)
Introduction/Main Objectives: analyze the Influence of Financial Ratios on Stock Returns with Dividend Policy as a Moderating Variable in Companies Listed on the IDX. Background ProblemsBecause energy consumption in Indonesia increased slightly by 0.4% compared to the previous year which was 905.6 million BOE and looking at the trend, domestic energy consumption tends to fluctuate over the past decade. Novelty: Retesting the same variables by previous researchers, because there are still differences in research between one study and another. Research Methods: This study uses a descriptive quantitative approach research type using secondary data on 11 companies out of 76 companies and the data analysis technique used is multiple linear regression with the help of the SPSS program. Findings/Results: The current ratio variable does not have a significant effect on stock returns and return on equity has a positive and significant effect on stock returns and the dividend payout ratio variable is unable to moderate the effect of the current ratio and return on equity on stock returns. Conclusion: Companies can improve company performance every year, and provide real and complete financial reports in order to attract investors so that it is easier to obtain capital from outside the company.